2014
DOI: 10.1109/jphot.2014.2366158
|View full text |Cite
|
Sign up to set email alerts
|

S-Band Gain Improvement Using a Thulium–Aluminum Co-Doped Photonic Crystal Fiber Amplifier

Abstract: An extended method for gain and noise figure enhancement in the S-band using a thulium-doped photonic crystal fiber amplifier (TD-PCFA) is proposed and shown by numerical simulation. The principle behind the enhancement is the suppression of unwanted amplified spontaneous emission (ASE) using the PCF structure. This proposed PCF achieves the intended band-pass by doping the cladding with high index material and realizes appropriate short and long cut-off wavelengths by enlarging the air-holes surrounding the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…A thermo-optic based bandwidth variable filter has been demonstrated theoretically and experimentally in [25]. In addition, bandpass filters using index-guiding holey PCF was numerically designed by changing the parameters of the core, background and air holes [26], [27]. Liu et al demonstrated the fabrication of a tunable bandpass filter by combining the bend loss edge of an all-solid PBGF and a Bragg fiber [28].…”
Section: Introductionmentioning
confidence: 99%
“…A thermo-optic based bandwidth variable filter has been demonstrated theoretically and experimentally in [25]. In addition, bandpass filters using index-guiding holey PCF was numerically designed by changing the parameters of the core, background and air holes [26], [27]. Liu et al demonstrated the fabrication of a tunable bandpass filter by combining the bend loss edge of an all-solid PBGF and a Bragg fiber [28].…”
Section: Introductionmentioning
confidence: 99%